Factors associated with growth status of Orang Asli children in Temerloh, Pahang, Malaysia - Wong, Chee Yen (2019)
Undernutrition continues to be the primary public health problem in Orang Asli (OA) children of Peninsular Malaysia. Most studies of undernutrition and it associated factors among indigenous children have been cross-sectional, but the relevance evidence from longitudinal studies is limited. The main objective of this study is to determine the factors associated with growth status of OA children in Temerloh, Pahang, and this study consisted of two phases. The first phase was a cross-sectional study (N=304) to determine the prevalence of undernutrition among children aged <5 years in 11 selected OA villages surrounding the Krau Wildlife Reserve, in Temerloh district of Pahang. The findings of the Phase 1 were used to support the implementation of the subsequent study, which was a 2-year prospective cohort study (N=214) to identify the pattern and timing of growth in children (aged ≤3 years) and its associated factors from seven selected Jah Hut villages in Temerloh district of Pahang. In the Phase 1 study, information were obtained from parents on household demographic and socio-economic, and child characteristics. Weight and length/height of children were also measured. Majority of children in this study were Jah Hut (86.4%) and living in poor households (75.9%). About 25% of children were born prematurely, and 32.2% had low birth weight. The prevalence of stunting, underweight, wasting and thinness among the OA children were 64%, 49%, 14% and 12%, respectively. In the Phase 2 study, data on household, maternal and child characteristics, dietary intake, caregiving behaviours, and common childhood illnesses were obtained from parents of children using a set of pre-tested interviewer-administered questionnaire and home observation checklist. Weight and length/height were also measured using standard procedures. There were 54.2% boys and 45.8% girls, in that 78% were from poor households. Approximately 31% of mothers had no formal education and 74% were housewives. About 14% of mothers had stature <145 cm, 8.9% were underweight and 28.5% were overweight/obese. A majority (76.6%) of children were born at health facilities, with average length and weight at birth of 48.18±2.63 cm and 2.66±0.44 kg, respectively. The rates of preterm birth and small for gestational age were 15.4% and 71%, respectively. Only 59.8% of children were breastfed within 1 hour of birth, 19.6% were exclusively breastfed for the first 6 months of life, and 44.4% started complementary food at 6 months of age. Most children (92–100%) did not achieve minimum acceptable diet during 6–60 months of age, in which only 0–55.6% of children achieved a minimum dietary diversity while the proportion of children achieving minimum meal frequency decreased with age (from 96.1% to 41.7%). At ages between 12 and 36 months, only 45–60% of children were responsibly fed by their mothers during lunch. The Jah Hut mothers were more affectionate and responsive (scores range: 9 to 10) to their children aged 6–24 months, but their interactions through encouragement and teaching (scores range: ≤7) were lacking during the first 5 years of age. The hygiene behaviour among the Jah hut community was generally satisfactory (scores range: 14.5 to 18.7), but safe garbage and faeces disposal, and hand washing with soap were not widely practiced. Most children (93%) received all immunizations based on the national immunization schedule. Between 6 and 30 months of age, a high proportion of children (35–41%) experienced certain common childhood illnesses in the past 2 weeks. About 20–29% of children did not seek treatment from health care provider or did not received any treatment when sick. This study showed that the Jah Hut children experienced faltering in length-for-age (LAZ) and weight-for-age (WAZ) during the first 2 years of life. In a multivariate analysis, children living in households with greater number of children (AOR: 1.16; 95% CI: 1.02–1.38) and whose mothers with height <145 cm (AOR: 7.53; 95% CI: 2.28–24.91) or 145–150 cm (AOR: 2.63; 95% CI: 1.34–5.14) and were delivered at home (AOR: 5.95; 95% CI: 2.26–15.69) were more likely to have an increased risk of stunting at the end of 2-year follow-up. The practice of responsive feeding during the 2–3 years of life (time 1) was protective against child stunting at ages 30–60 months of age (AOR: 0.63; 95% CI: 0.41–0.96). Children aged 6–36 months who were in the lowest tertile of hygiene behaviours (time 1) had 4.2 times greater risk of being stunted at ages 30–60. For mother-child interactions, the likelihood of being stunted at ages 30–60 months was 5.25–7.44 times higher among children aged 18–48 months (time 3) who were in the Tertile 1 and 2 than those in the Tertile 3. Moreover, children aged 24–54 months who experienced certain common childhood illness in the past 2 weeks (time 4) were 3.52 times more likely to be stunted at ages 30–60 months. In conclusion, stunting remains as the most prevalent form of undernutrition among the under-five OA children (Phase 1), with a faltering in LAZ during the first 2 year of life was more pronounced than WAZ (Phase 2). Therefore, the first 2 years of life is a “window of opportunity” to promote optimal linear growth in OA children. Implementation of nutrition-specific and -sensitive interventions during this critical period could prevent early growth retardation and subsequently improve health and well-being of OA children. This study also underscores the important advantage of having early prevention (before or/and during pregnancy) and reinforcing family planning program to break the vicious intergeneration cycle of malnutrition.